eIF3 controls cell size independently of S6K1-activity - Schipany, Katharina (Oncotarget, 2015)
All multicellular organisms require a life-long regulation of the number and the size of cells, which build up their organs. mTOR acts as a signaling nodule for the regulation of protein synthesis and growth. To activate the translational cascade, mTOR phosphorylates S6 kinase (S6K1), which is liberated from the eIF3-complex and mobilized for activation of its downstream targets. How S6K1 regulates cell size remains unclear. Here, we challenged cell size control through S6K1 by specifically depleting its binding partner eIF3 in normal and transformed cell lines. We show that loss of eIF3 leads to a massive reduction of cell size and cell number accompanied with an unexpected increase in S6K1-activity. The hyperactive S6K1-signaling was rapamycin-sensitive, suggesting an upstream mTOR-regulation. A selective S6K1 inhibitor (PF-4708671) was unable to interfere with the reduced size, despite efficiently inhibiting S6K1-activity. Restoration of eIF3 expression recovered size defects, without affecting the p-S6 levels. We further show that two, yet uncharacterized, cancer-associated mutations in the eIF3-complex, have the capacity to recover from reduced size phenotype, suggesting a possible role for eIF3 in regulating cancer cell size. Collectively, our results uncover a role for eIF3-complex in maintenance of normal and neoplastic cell size - independent of S6K1-signaling.